Smoking marijuana and the risk of psychiatric re-hospitalization of patients with schizophrenia - Pawełczak, Paweł; Karakuła, Hanna; Wróbel, Aleksandra; Tomkiewicz, Katarzyna (Current Problems of Psychiatry, 2013)
Cannabis is the most frequently used drug by people suffering from schizophrenia, and its use in this group is comparatively higher than in the whole population. Schizophrenia is a chronic mental disorder characterised by high probability of relapsing into the illness and recurrent hospitalisation. One of the directions for studies, which aim at finding connections between the use of cannabis and schizophrenia, is the question of influence of cannabis use onto the risk of psychiatric recurrent hospitalisation. In this thesis, a survey of available publications – dwelling on the subject of influence of cannabis use by schizophrenia-suffering individuals onto the risk of recurrent hospitalisation – was conducted. Studies carried out up to date indicate that cannabis use may constitute a significant risk factor for schizophrenia relapse. It is difficult to define exact mechanism of influence of cannabis use onto the risk of hospitalisation, as connections between cannabis use and psychotic states are very complex. Studies that estimate connection between cannabis use and intensification of schizophrenia symptoms are not conclusive. On the other hand, it is stressed that cannabis use has a connection with an earlier age of schizophrenia onset and a worse patients’ compliance, which may lead to higher risk of illness relapse and recurrent hospitalisation. Hitherto studies indicate that cannabis use may have essential influence onto the course of schizophrenia and its prognosis, which should prompt further studies.